Towards the development of performance appraisal system for vcc senior and junior staff: Towards the development of performance appraisal system for vcc senior and junior staff (Journal of Educational Management, 2000)
The principal aim of this study was to evaluate the current VCC performance appraisal for the Junior and Senior Staff and to make recommendations for improvement or development of a new system for consideration by management. The study revealed that an effective performance appraisal system must, among other things, aim at: • Performance Improvement • Compensation Adjustments • Placement Decisions • Training and Development of Staff • Identification of Deficiencies in Staffing Process. Preparations to meet external Challenges It also revealed that management and staff use the feedback from the appraisal exercise in making important management and personal decisions including career planning Q/~d Human Resource Planning. The study further revealed that the VCC Junior and Senior Staff appraisal system document suffers from a number of problems and that there is the need to design a--l1e;V appraisal system for the assessment of VCC Junior and Senior Staff work performance. From the findings of the study, it is proposed for consideration by management, Peter Druker Management by Objectives (MBO) technique. Though this technique does not represent the ideal form of performance appraisal technique (Luthan I977), it is one of the techniques that come closest to the ideal. It represents a significant point of departure ji-om the rating scale and offers a great deal of potential for the future.